Performance landscape modeling in digital manufacturing firm. Issue 3 (27th June 2019) - Kulkarni, Sourabh; Verma, Priyanka; Mukundan, R.
Abstract : Purpose: The purpose of this paper is to update existing Kauffmann's NK model to evaluate the manufacturing fitness of strategic business capabilities. The updated model is tested in a digital manufacturing (DM) setting to investigate the sequence for developing cumulative capabilities that can yield the maximum payoff. Design/methodology/approach: The authors develop a grey–DEMATEL–NK fitness model and show its application, through a case study, to a DM firm in India. Findings: The grey–DEMATEL–NK model helps evaluate multiple manufacturing capabilities and indicates that quality–flexibility–cost–delivery is the sequence that yields the maximum manufacturing fitness (competitive payoff) for a DM firm. This sequence helps the firm reorganise its internal business processes and is different from that used to develop cumulative capabilities in a traditional manufacturing setting (quality–delivery–flexibility–cost). Originality/value: This study presents a pilot model for computing the cumulative capabilities payoff and prescribes a sequence for developing cumulative capabilities within a DM context.